2012
DOI: 10.1111/omi.12012
|View full text |Cite
|
Sign up to set email alerts
|

Microbial interactions in building of communities

Abstract: SUMMARY Establishment of a community is considered to be essential for microbial growth and survival in the human oral cavity. Biofilm communities have increased resilience to physical forces, antimicrobial agents, and nutritional variations. Specific cell-to-cell adherence processes, mediated by adhesin-receptor pairings on respective microbial surfaces, are able to direct community development. These interactions co-localize species in mutually beneficial relationships, such as streptococci, veillonellae, Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
163
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(170 citation statements)
references
References 156 publications
(185 reference statements)
2
163
0
5
Order By: Relevance
“…Previous studies have shown that P. gingivalis interacts with primary colonizing organisms such as S. gordonii 22,23 and that this interaction may be an initial event that facilitates P. gingivalis colonization of the oral cavity. As such, it represents an ideal target for therapeutic intervention to limit P. gingivalis colonization.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that P. gingivalis interacts with primary colonizing organisms such as S. gordonii 22,23 and that this interaction may be an initial event that facilitates P. gingivalis colonization of the oral cavity. As such, it represents an ideal target for therapeutic intervention to limit P. gingivalis colonization.…”
Section: Discussionmentioning
confidence: 99%
“…Close proximity or physical contact between two microbes can substantially alter their physiology, for example conferring on an anaerobe the ability to survive in an aerobic environment (1) or dramatically altering the range of metabolites produced compared with those produced by the same organism in isolation (2)(3)(4)(5). Thus, a mechanistic understanding of the physiology of key players depends on knowing the identity of the neighbors with which they commonly interact.…”
mentioning
confidence: 99%
“…These species of streptococci interact with a range of other oral microorganisms, thus establishing a foundation for the building of biofilm communities (Wright et al, 2013). S. gordonii forms biofilms with Porphyromonas gingivalis (Lamont et al, 2002), Actinomyces oris (Palmer et al, 2003), Fusobacterium nucleatum (Foster & Kolenbrander, 2004) and Aggregatibacter actinomycetemcomitans in dual or mixed species systems, and also produces dual species biofilms with the fungus Candida albicans (Bamford et al, 2009;Dutton et al, 2014).…”
Section: Introductionmentioning
confidence: 99%